PEMBUATAN PUPUK ORGANIK DARI SAMPAH RUMAH TANGGA DI PERUMAHAN BUKIT DEWA RESIDENCE KOTA BENGKULU - Deni Agus Triawan; Dyah Fitriani; Nesbah Nesbah (LPPM IST AKPRIND Yogyakarta, 2020)
Increasing the amount of waste with the imbalance of the management process will make the problem bigger. In the waste management hierarchy, prevention is the highest component. However, if prevention cannot be carried out, management with reuse of waste can be an option. One of them is the use of household waste into useful products. The aim of this community service to give information about organic fertilizer made from organic household wastes at Bukit Dewa Residence, City of Bengkulu. Several methods including lectures, discussions, demonstrations, direct practice and observation were used. Making composter for household waste processing into organic fertilizer that will be carried out refers to the composter that has been studied and sought by the Departemen Pekerjaan Umum, Bandung Regency. The result of this program had been seen by the level of participation and the product were prepared. The skills of participants in the manufacture of these products are conveyed by direct practice methods with the guidance of the speaker. Organic fertilizer that has been produced will be used for ornamental plants and garden plants, thereby reducing the cost of purchasing chemical fertilizers.